Which students can reach higher proficiency in speaking and reading those taking classes a blended learning a approach versus those taking classes a face- to face approach in advanced intensive english I at Foreign Language Department of the University of El Salvador during year 2014 - Molina Cruz, Wilson Jonathan
This research is very significant as it will help to improve not only the Intensive Advanced English I courses, but also, its findings could be applied to other courses where a blended approach is applied. We aim to test whether or not the reading and speaking skills studied in the Intensive English Advance I courses are put into practice.